Iron phosphate material, preparation method thereof and lithium iron phosphate material

The iron phosphate material was prepared through two precipitation reactions, and the oxidation rate of ferrous ions and the outer pore structure were controlled, which solved the problem of insufficient tap density and specific surface area of ​​lithium iron phosphate material, and achieved high energy density and good ion diffusion efficiency.

CN119774569AActive Publication Date: 2025-04-08GUANGDONG BRUNP RECYCLING TECH CO LTD +1

Patent Information

Application Number
CN202411922498.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing lithium iron phosphate materials have shortcomings in tap density and specific surface area, which affects their energy density and ion diffusion efficiency.

Method used

The iron phosphate material was prepared by two precipitation reactions. The first step was to control the oxidation rate of ferrous ions to form dense core particles; the second step was to add citric acid and oxygen to form a uniformly distributed outer pore structure.

Benefits of technology

The goal of iron phosphate materials having high tap density and high specific surface area has been achieved, the energy density and ion diffusion efficiency of the battery are improved, and the content of impurity elements is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774569A_ABST
    Figure CN119774569A_ABST
Patent Text Reader

Abstract

The invention discloses an iron phosphate material, a preparation method thereof and a lithium iron phosphate material, and belongs to the field of positive electrode materials. The iron phosphate material provided by the invention comprises a porous outer layer, the pore area ratio of micropores to mesopores to macropores of the iron phosphate material is (10%-20%): (55%-65%): (20%-30%); the pore diameter of the iron phosphate material is mainly mesopores, and the positions of outer layer pores are uniformly distributed, so that the iron phosphate material has good tap density and specific surface area. The iron phosphate material with the structure is prepared through two precipitation reactions; the method comprises the following steps: firstly, obtaining core particles with relatively few pores through a primary precipitation reaction; and preparing an outer layer with relatively many pores and low impurity elements by taking the inner core particles obtained by the primary precipitation reaction as seed crystals and controlling the addition amount of citric acid and the introduction rate of oxidizing gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of positive electrode materials, and in particular to an iron phosphate material and a preparation method thereof, and a lithium iron phosphate material. Background Art

[0002] In recent years, the new energy industry has developed rapidly. Among them, lithium-ion batteries have been widely used in power batteries and energy storage materials due to their advantages such as high specific energy, high power density and long life. At the same time, compared with traditional positive electrode materials such as lithium cobalt oxide and lithium manganese oxide, lithium iron phosphate materials have the advantages of stable structure, high safety performance, good cycle performance, wide source of raw materials and low cost, making lithium iron phosphate one of the most ideal positive electrode materials for power batteries.

[0003] At present, tap density, specific surface area and impurity element content have an important influence on the performance of lithium iron phosphate materials. Specifically, increasing the tap density of the material is an effective means to increase the energy density per unit volume of the battery; the specific surface area is also a factor affecting the performance of lithium iron phosphate. The smaller the specific surface area, the smaller the contact area between the particles and the longer the diffusion path of the ions; in addition, the impurity elements in iron phosphate also affect the performance of the obtained lithium iron phosphate material, among which the sulfur element has a significant effect on the particle morphology, discharge capacity and cycle performance of lithium iron phosphate, and needs to be controlled in a lower range. Iron phosphate is an important precursor of lithium iron phosphate materials, and lithium iron phosphate materials inherit the morphology, structure and properties of iron phosphate. Therefore, iron phosphate materials have high specific surface area, high tap density and low impurity content, which is conducive to improving the energy density of lithium iron phosphate batteries.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention includes providing an iron phosphate material and a preparation method thereof and a lithium iron phosphate material, wherein the iron phosphate material provided has both solid density and specific surface area.

[0006] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides an iron phosphate material, which includes a porous outer layer; and the pore area ratio of micropores, mesopores and macropores of the iron phosphate material satisfies 10%-20%:55%-65%:20%-30%.

[0007] In some embodiments, the iron phosphate material satisfies at least one of the following features 1-3: Feature 1: The specific pore volume of the iron phosphate material is 0.06-0.10cm 3 / g; Feature 2: The tap density of the iron phosphate material is 1.15-1.35 g / cm 3 ; Feature 3: The specific surface area of ​​the iron phosphate material is 6.40-7.30m 2 / g.

[0008] The second aspect of the present invention provides a method for preparing the iron phosphate material provided by the first aspect of the present invention, comprising: A primary precipitation reaction: partially oxidizing the ferrous ions in the ferrous salt solution into trivalent ferrous ions, and adding a portion of the phosphorus source to perform a primary precipitation reaction to obtain a primary slurry; Secondary precipitation reaction: adding citric acid to the primary slurry, then blowing in oxygen or air and adding the remaining phosphorus source to carry out secondary precipitation reaction, and after solid-liquid separation, washing and drying to obtain hydrated iron phosphate; Calcination: The hydrated ferric phosphate is calcined to obtain ferric phosphate material.

[0009] In some embodiments, the partial oxidation refers to oxidizing 5%-20% of the ferrous ions in the ferrous salt solution into ferric ions; And / or, the sulfur content percentage of the hydrated ferric phosphate material is 0.0125wt%-0.0150wt%.

[0010] In some embodiments, the amount of citric acid added is 1wt%-8wt% of the theoretical yield of ferric phosphate; Preferably, the amount of citric acid added is 1wt%-4wt% of the theoretical output of ferric phosphate.

[0011] In some embodiments, the partial oxidation comprises adding hydrogen peroxide to the ferrous salt solution at a rate of 0.2-0.5 L / h; And / or, the blowing flow rate of the oxygen or air is 10-30 L / h.

[0012] In some embodiments, the ferrous salt in the ferrous salt solution includes at least one of ferrous sulfate, ferrous chloride and ferrous nitrate; And / or, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium phosphate.

[0013] In some embodiments, the concentration of iron in the ferrous salt solution is 0.8-1.2 mol / L; And / or, the molar ratio of phosphorus in the phosphorus source to iron in the ferrous salt solution is 1:1.0-1.1.

[0014] In some embodiments, the temperature of the first precipitation reaction and the second precipitation reaction are both 90-98°C; And / or, the primary precipitation reaction includes keeping warm for 1-3 hours after stopping the feeding; And / or, the secondary precipitation reaction includes aging for 3-6 hours after stopping the feeding; And / or, the calcination temperature is 600-750° C., and the calcination time is 2-6 hours.

[0015] The third aspect of the present invention provides a lithium iron phosphate material, which is prepared from the iron phosphate material provided by the first aspect of the present invention or the iron phosphate material obtained by the preparation method provided by the second aspect of the present invention.

[0016] The beneficial effects of the present invention include: The iron phosphate material provided by the present invention has a porous outer layer, and the positions of the pores are evenly distributed; the interior of the iron phosphate material is relatively dense and the outer layer is relatively loose, and the pore size of the material is mainly mesopores, so that the iron phosphate material has both good tap density and specific surface area.

[0017] The preparation method provided by the present invention prepares the ferric phosphate material with the above structure through two precipitation reactions; during the first precipitation reaction, the oxidation rate of ferrous ions in a ferrous salt solution is controlled to obtain inner core particles with relatively fewer pores, which is beneficial to improving the overall tap density and structural stability of the material; during the second precipitation reaction, the particles obtained by the first precipitation reaction are used as crystal seeds, and the amount of citric acid added and the introduction rate of oxidizing gas are controlled to obtain an outer layer with relatively more pores and low impurity elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a SEM image of the iron phosphate slice provided in Example 1 of the present invention; Figure 2 This is a SEM image of the iron phosphate slice provided in Comparative Example 1 of the present invention; Figure 3 The XRD pattern of ferric phosphate dihydrate provided in Example 1 of the present invention; Figure 4 This is the XRD diagram of the iron phosphate provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0020] Hereinafter, an iron phosphate material and a preparation method thereof and a lithium iron phosphate material of the present invention are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0021] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. In particular, "()", ")", "[" and "]" represent intervals, where "(" or ")" represents an open interval, that is, the endpoint values ​​of the interval are not included; "[" and "]" represent a closed interval, that is, the endpoints within the interval are included. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0022] Specifically, for example, if the range of 60-120 and 80-110 is listed for a particular parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just the abbreviation of these numerical combinations. In addition, when stating that a certain parameter is an integer of ≥2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. If (10, 20) is listed, it is understood as any value between 10 and 20, excluding 10 and 20; (10, 20] is understood as any value between 10 and 20, excluding 10 but including 20.

[0023] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0024] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0025] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0026] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0027] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0028] A first aspect of the present invention provides an iron phosphate material, comprising a porous outer layer; and the pore area ratio of micropores, mesopores and macropores of the iron phosphate material satisfies 10%-20%:55%-65%:20%-30%.

[0029] Among them, the pore size of the micropores is 0.35-2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is 50-170nm; the pore area refers to the total area of ​​the pore surface per unit mass of the material, and the pore area of ​​the mesopores refers to the total area of ​​the mesoporous surface per unit mass of the material, which is tested by the static capacity method and calculated by the BET multi-point method; unless otherwise specified, the iron phosphate materials described in the present invention are all anhydrous iron phosphate.

[0030] The iron phosphate material provided by the present invention has a double-layer structure, including a relatively dense inner core and a relatively loose outer layer, and the inner tight and outer loose structure enables it to have a good specific surface area and a good tap density. In addition, the pores in the outer layer are mainly mesopores, and the positions of the pores are evenly distributed, which is conducive to improving the ion diffusion and charge transfer efficiency of the positive electrode material prepared thereby.

[0031] It can be understood that the lithium iron phosphate material includes a core and an outer shell, the outer shell is porous, and the porosity of the outer shell is higher than that of the inner core; the inner core is the iron phosphate in the central part, and the outer shell is the iron phosphate close to the outer surface, i.e., the outer layer.

[0032] In some embodiments, the specific pore volume of the iron phosphate material is 0.06-0.10 cm 3 / g.

[0033] The specific pore volume refers to the volume of pores per unit mass of material, which is tested by static capacity method and calculated by BET multi-point method. The specific pore volume of the iron phosphate material is the total specific pore volume of mesopores, micropores and macropores.

[0034] The second aspect of the present invention provides a method for preparing the ferric phosphate material provided in the first aspect, comprising: a primary precipitation reaction: partially oxidizing ferrous ions in a ferrous salt solution into trivalent ferrous ions, adding a portion of a phosphorus source, and performing a primary precipitation reaction to obtain a primary slurry; Secondary precipitation reaction: adding citric acid to the primary slurry, then blowing in oxygen or air and adding the remaining phosphorus source to carry out secondary precipitation reaction, and after solid-liquid separation, washing and drying to obtain hydrated iron phosphate; Calcination: The hydrated ferric phosphate is calcined to obtain ferric phosphate material.

[0035] The primary precipitation reaction includes continued heat preservation after the addition of materials is completed. Heat preservation is conducive to obtaining a seed crystal with a stable structure and is conducive to the secondary precipitation reaction on the surface of the seed crystal. The addition of citric acid in the secondary precipitation reaction can balance the dissolution and recrystallization process of the surface of the hydrated ferric phosphate during its growth, which is conducive to the uniform growth of the outer pore structure; the use of oxygen or air as an oxidant in the secondary precipitation reaction reduces the precipitation rate of the secondary precipitation reaction, which is conducive to the formation of a uniform pore distribution in the outer layer of the ferric phosphate, and also reduces the accumulation of impurity elements in the growth process of the ferric phosphate, while greatly reducing the cost.

[0036] In the two-stage precipitation reaction, the seeds formed during the first precipitation reaction continue to grow on the surface of the seeds in the second precipitation reaction using citric acid and oxidizing gas. The resulting iron phosphate particles are relatively dense inside and relatively loose on the outside, and the pores in the outer layer are evenly distributed. Therefore, the obtained lithium iron phosphate material has good overall dispersion and regular morphology, which makes it have both high specific surface area and high tap density.

[0037] In some embodiments, partial oxidation refers to oxidizing 5%-20% of the ferrous ions in the ferrous salt solution into ferric ions.

[0038] If the oxidation rate of ferrous ions in the ferrous salt solution is too low, the particles will become larger and the specific surface area will become smaller during the subsequent induction process; if the oxidation rate of ferrous ions in the ferrous salt solution is too high, the inner core will become larger, which is not conducive to the uniform distribution of the outer shell pores. By controlling the oxidation amount of ferrous ions during the first precipitation reaction, the size of the central part of the iron phosphate material can be controlled; the second precipitation reaction forms an outer layer of iron phosphate material with a higher porosity and uniform pore distribution relative to the central part.

[0039] In some embodiments, the sulfur content percentage of the hydrated ferric phosphate is 0.0125 wt % to 0.0150 wt %.

[0040] In some embodiments, the Al element content in the hydrated ferric phosphate is 0.004wt%-0.008wt%; the Ca element content in the hydrated ferric phosphate is 0.0005wt%-0.0012wt%; and the Ti element content in the hydrated ferric phosphate is 0.0005wt%-0.0015wt%.

[0041] It should be noted that impurity elements such as Al, S, Ca, Ti, etc. come from external pollution in the raw materials or the preparation process. These impurity elements have a great influence on the capacity and cycle performance of the subsequent lithium iron phosphate material prepared from the iron phosphate material. In particular, the S element has a significant effect on the morphology, discharge capacity and cycle performance of the subsequent lithium iron phosphate material. Therefore, it is of great significance to obtain iron phosphate materials with low impurity elements.

[0042] In some embodiments, the amount of citric acid added is 1 wt%-8 wt% of the theoretical yield of ferric phosphate; Preferably, the amount of citric acid added is 1 wt%-4 wt% of the theoretical output of ferric phosphate.

[0043] The theoretical yield of ferric phosphate is the theoretical yield of ferric phosphate that can be produced from ferrous salt in ferrous salt solution. An appropriate amount of citric acid is beneficial to the dissolution and recrystallization of the seed crystal surface during the secondary precipitation process, forming a uniform pore size on the outer layer of ferric phosphate; however, excessive citric acid content will affect the precipitation efficiency and cause the outer core pores to become larger; at the same time, too low citric acid content cannot significantly reduce impurities and will also cause uneven distribution of outer core pores.

[0044] In some embodiments, a precipitation reaction includes keeping warm for 1-3 hours after stopping the addition of materials.

[0045] Insulation is beneficial to making the seeds obtained by the primary precipitation reaction more stable, and is beneficial to obtaining iron phosphate materials with high tap density and high specific surface area by the secondary precipitation reaction.

[0046] In some embodiments, the secondary precipitation reaction includes aging for 3-6 hours after stopping the feeding. After aging, the slurry is filtered, washed, and dried to obtain hydrated iron phosphate; wherein the washing is performed until the conductivity of the washing water is less than 500 μS / cm; and the drying temperature is 90-120°C.

[0047] In some embodiments, the first precipitation reaction and the second precipitation reaction include stirring, and the stirring speed is 600-900 rpm.

[0048] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0049] The features and properties of the present invention are further described in detail below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0050] Example 1 Primary precipitation reaction: Add 1.0 mol / L ferrous sulfate solution into the reactor, heat it to 90°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 2 h to obtain a slurry.

[0051] The concentration of the phosphoric acid solution is 1.0 mol / L; the flow rate of the hydrogen peroxide solution is 0.2 L / h.

[0052] Secondary precipitation reaction: Add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, then introduce oxygen into the reactor at a flow rate of 15L / h, and add phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1, the addition is stopped and the temperature is kept warm for 6 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0053] Among them, the amount of citric acid added is 2wt% of the theoretical output of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution is 1.0mol / L; in this example and the following examples, the "total molar amount of phosphoric acid" refers to the total molar amount of phosphoric acid added in the primary precipitation reaction and the secondary precipitation reaction; the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction is 700rpm.

[0054] Calcination reaction: Calcine the hydrated iron phosphate at 650°C for 4 hours to obtain the iron phosphate material.

[0055] Example 2 The iron phosphate material was prepared according to the method of Example 1, and other conditions were the same, except that: in one precipitation reaction, the addition of materials was stopped and the temperature was kept for 3 hours; The amount of citric acid added is 4 wt% of the theoretical yield of ferric phosphate (calculated as ferrous salt).

[0056] Example 3 Primary precipitation reaction: Add 1.2 mol / L ferrous sulfate solution into the reactor, heat it to 95°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 20% and the molar amount of phosphoric acid added is about the same as Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 1 hour to obtain a slurry.

[0057] The concentration of the phosphoric acid solution is 1.1 mol / L; the flow rate of the hydrogen peroxide solution is 0.2 L / h.

[0058] Secondary precipitation reaction: Add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, then introduce oxygen into the reactor at a flow rate of 15L / h, and add phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1, the addition is stopped and the aging is continued for 4 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm, and dried at 105°C to obtain hydrated iron phosphate.

[0059] The amount of citric acid added was 2 wt % of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution was 1.1 mol / L; and the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0060] Calcination reaction: Calcine the hydrated iron phosphate at 650° C. for 4 h to obtain the iron phosphate material.

[0061] Example 4 The iron phosphate material was prepared according to the method of Example 1, and other conditions were the same, except that: the amount of citric acid added was 1wt% of the theoretical yield of iron phosphate (calculated as ferrous salt); In the secondary precipitation reaction, the mixture was kept warm for 4 h; The hydrated iron phosphate was calcined at 700°C for 4 h.

[0062] Example 5 Primary precipitation reaction: Add 1.0 mol / L ferrous sulfate solution into the reactor, heat it to 98°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 1 hour to obtain a slurry.

[0063] The concentration of the phosphoric acid solution is 0.9 mol / L; the flow rate of the hydrogen peroxide solution is 0.2 L / h.

[0064] Secondary precipitation reaction: Add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, then introduce oxygen into the reactor at a flow rate of 15L / h, and add phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1, the addition is stopped and the temperature is kept warm for 3 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0065] The amount of citric acid added was 3 wt % of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution was 0.9 mol / L; and the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0066] Calcination reaction: Calcine the hydrated iron phosphate at 750°C for 4 hours to obtain the iron phosphate material.

[0067] Example 6 Primary precipitation reaction: Add 1.0 mol / L ferrous sulfate solution into the reactor, heat it to 98°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 1 hour to obtain a slurry.

[0068] The concentration of the phosphoric acid solution is 1.0 mol / L; the flow rate of the hydrogen peroxide solution is 0.2 L / h.

[0069] Secondary precipitation reaction: Add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, then introduce oxygen into the reactor at a flow rate of 15L / h, and add phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1, the addition is stopped and the aging is continued for 4 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm, and dried at 105°C to obtain hydrated iron phosphate.

[0070] The amount of citric acid added was 6wt% of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution was 1.0 mol / L; and the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700rpm.

[0071] Calcination reaction: Calcine the hydrated iron phosphate at 650° C. for 4 h to obtain the iron phosphate material.

[0072] Example 7 Primary precipitation reaction: Add 0.8 mol / L ferrous sulfate solution into the reactor, heat it to 90°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 5% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the amount of 2-nitropropene (2-nitropropene) to the amount of 2-nitropropene (2-nitropropene) obtained by oxidation is 1:1.05, the addition of the material is stopped and the temperature is kept for 2 hours to obtain a slurry.

[0073] The concentration of the phosphoric acid solution is 1.0 mol / L; the flow rate of the hydrogen peroxide solution is 0.35 L / h.

[0074] Secondary precipitation reaction: add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, then introduce air into the reactor at a flow rate of 10L / h, and add phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1.05, the addition is stopped and the temperature is kept warm for 6 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0075] The amount of citric acid added was 2 wt % of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution was 1.0 mol / L; and the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0076] Calcination reaction: Calcine the hydrated iron phosphate at 700°C for 2h to obtain the iron phosphate material.

[0077] Example 8 Primary precipitation reaction: Add 1.0 mol / L ferrous sulfate solution into the reactor, heat it to 90°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1.1, the addition of the reaction mixture is stopped and the mixture is kept warm for 2 h to obtain a slurry.

[0078] The concentration of the phosphoric acid solution is 1.0 mol / L; the flow rate of the hydrogen peroxide solution is 0.5 L / h.

[0079] Secondary precipitation reaction: Add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, then introduce air into the reactor at a flow rate of 30L / h, and add phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1.1, the feeding is stopped and the temperature is kept warm for 6 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0080] The amount of citric acid added was 2 wt % of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution was 1.0 mol / L; and the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0081] Calcination reaction: Calcine the hydrated iron phosphate at 600°C for 6 hours to obtain the iron phosphate material.

[0082] Comparative Example 1 The iron phosphate material was prepared according to the method of Example 1, and other conditions were the same, except that citric acid was not added during the secondary precipitation reaction; No air was introduced, hydrogen peroxide was used as an oxidant, and phosphoric acid solution was added to carry out precipitation reaction.

[0083] Comparative Example 2 Primary precipitation reaction: Add 1.0 mol / L ferrous sulfate solution into the reactor, heat it to 95°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 2 h to obtain a slurry.

[0084] The concentration of the phosphoric acid solution is 1.0 mol / L; the flow rate of the hydrogen peroxide solution is 0.2 L / h.

[0085] Secondary precipitation reaction: Add citric acid to the slurry obtained from the first precipitation reaction and stir evenly, and continue to add hydrogen peroxide and phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1, the addition is stopped and the temperature is kept warm for 6 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0086] The amount of citric acid added was 0.5 wt % of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution was 1.0 mol / L; and the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0087] Calcination reaction: Calcine the hydrated iron phosphate at 700°C for 4 hours to obtain the iron phosphate material.

[0088] Comparative Example 3 Primary precipitation reaction: Add 1.0 mol / L ferrous sulfate solution into the reactor, heat it to 80°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react until Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 3 h to obtain a slurry.

[0089] The concentration of the phosphoric acid solution is 1.0 mol / L; the flow rate of the hydrogen peroxide solution is 0.2 L / h.

[0090] Secondary precipitation reaction: Continue to add the remaining hydrogen peroxide and phosphoric acid solution to carry out precipitation reaction until the divalent iron ions are completely oxidized and the total molar amount of phosphoric acid added is equal to the Fe in the ferrous salt. 2+When the molar ratio is 1:1, the addition is stopped and the temperature is kept warm for 6 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0091] The concentration of the phosphoric acid solution was 1.0 mol / L; the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0092] Calcination reaction: Calcine the hydrated iron phosphate at 750°C for 4 hours to obtain the iron phosphate material.

[0093] Comparative Example 4 The iron phosphate material was prepared according to the method of Example 1, with other conditions being the same, except that citric acid was not added in the secondary precipitation reaction.

[0094] Comparative Example 5 The iron phosphate material was prepared according to the method of Example 1, and other conditions were the same, except that: no heat preservation reaction was performed in the first precipitation reaction; No citric acid was added in the secondary precipitation reaction.

[0095] Comparative Example 6 Primary precipitation reaction: After adding 1.0 mol / L ferrous sulfate solution into the reactor, add citric acid, heat to 90°C, and add 30% mass percent hydrogen peroxide and phosphoric acid solution into the reactor to react. Control the Fe 2+ The oxidation rate is 10% and the molar amount of phosphoric acid added is equal to Fe 3+ (Fe 2+ When the molar ratio of the reaction mixture to that obtained by oxidation is 1:1, the addition of the reaction mixture is stopped and the mixture is kept warm for 2 h to obtain a slurry.

[0096] The amount of citric acid added is 2 wt% of the theoretical yield of ferric phosphate (calculated as ferrous salt); the concentration of the phosphoric acid solution is 1.0 mol / L; and the flow rate of hydrogen peroxide is 0.2 L / h.

[0097] Secondary precipitation reaction: Then, oxygen was introduced into the reactor at a flow rate of 15 L / h, and phosphoric acid solution was added to carry out precipitation reaction until the divalent iron ions were completely oxidized and the total molar amount of phosphoric acid added was equal to the Fe in the ferrous salt. 2+ When the molar ratio is 1:1, the addition is stopped and the temperature is kept warm for 6 hours. After the solid-liquid separation of the obtained slurry, it is washed until the conductivity of the washing water is 400 μS / cm and dried at 105°C to obtain hydrated iron phosphate.

[0098] The concentration of the phosphoric acid solution was 1.0 mol / L; the stirring speed of the reactor during the primary precipitation reaction and the secondary precipitation reaction was 700 rpm.

[0099] Calcination reaction: Calcine the hydrated iron phosphate at 650° C. for 4 h to obtain the iron phosphate material.

[0100] Comparative Example 7 The ferric phosphate material was prepared according to the method of Example 1, with other conditions being the same, except that: the Fe 2+ The oxidation rate is 3%; The hydrated iron phosphate was calcined at 700°C for 4 hours to obtain an iron phosphate material.

[0101] Comparative Example 8 The ferric phosphate material was prepared according to the method of Example 1, with other conditions being the same, except that: the Fe 2+ The oxidation rate is 40%; The hydrated iron phosphate was calcined at 700°C for 4 hours to obtain an iron phosphate material.

[0102] Comparative Example 9 The iron phosphate material was prepared according to the method of Example 1, with other conditions being the same, except that a 30% by mass concentration of hydrogen peroxide was used in the secondary precipitation reaction process, and oxygen oxidation was not used.

[0103] [Testing of parameters related to hydrated iron phosphate and iron phosphate materials] 1. Morphological characterization The iron phosphate samples of the embodiments and comparative examples were tested using a scanning electron microscope. Figure 1 This is a SEM image of a slice of the iron phosphate material obtained in Example 1. It can be seen that the inside of the iron phosphate particles is relatively compact, and the outer layer of the iron phosphate particles has pores with uniform pore size and uniform distribution; Figure 2 This is a SEM image of the iron phosphate slice prepared in Comparative Example 1. It can be seen that the pore sizes of the outer layer of the iron phosphate particles are different and the pore distribution uniformity is relatively poor.

[0104] 2. Phase detection The hydrated iron phosphate and the iron phosphate sample of Example 1 were tested using an X-ray diffractometer. Figure 3 This is the XRD diagram of the hydrated iron phosphate material prepared in Example 1. It can be seen that the hydrated iron phosphate is a pure monoclinic crystal without other impurities. The corresponding standard card is PDF#33-0666; Figure 4 This is the XRD diagram of the iron phosphate material prepared in Example 1. It can be seen that when calcined at this temperature, the iron phosphate is completely crystallized without the presence of impurities.

[0105] 3. Specific surface area test The specific surface area of ​​the iron phosphate material in each embodiment and comparative example was analyzed and calculated by BET multi-point method using a BSD-660S A6B6 specific surface area tester. The test results of each embodiment and comparative example are shown in Table 2.

[0106] 4. Element content test The element content of the iron phosphate material of each embodiment and comparative example was tested by inductively coupled plasma emission spectrometry: the iron phosphate material and the hydrated iron phosphate material were first digested and then diluted by the corresponding multiples according to the content for testing. The elements were tested by the HG / T4701-2021 standard titration method. The test results of each embodiment and comparative example are shown in Tables 1 and 2.

[0107] 5. Tap density test According to GB / T 5162-2006, the lithium iron phosphate materials of each embodiment and comparative example were tested using a tap density tester BT-302. The test results of each embodiment and comparative example are shown in Table 2.

[0108]

[0109]

[0110] It can be seen from Table 2 that, compared with Comparative Examples 1-9, the pore area ratio of the mesopores and mesopores in Examples 1-8 is higher than that of the micropores and mesopores, while the pore area ratio of the macropores is lower, and the specific pore volume value is larger. The corresponding iron phosphate material has a high specific surface area and a good tap density. Combining Tables 1 and 2, it can be seen that the impurity element content of the hydrated iron phosphate obtained in Example 1 is low, wherein the sulfur (S) element content is only 0.0129wt%, and the specific surface area of ​​the obtained iron phosphate material is as large as 7.26m 2 / g, the tap density is as high as 1.3g / cm 3 As can be seen from Examples 2-8, the impurity elements of the hydrated iron phosphate material prepared by the preparation method provided by the present invention are relatively low, wherein the sulfur (S) element content is 0.0129-0.0143wt%, and the specific surface area of ​​the iron phosphate material is 6.48-7.26 m 2 / g, tap density is 1.19-1.30 g / cm 3 .

[0111] Compared with Example 1, in Comparative Example 4, no citric acid was added during the secondary precipitation reaction, and the content of S element in the obtained hydrated iron phosphate material was 0.0242wt%; the specific surface area and tap density of the obtained iron phosphate material were both reduced, which were 7.14 m 2 / g and 1.19 g / cm 3Compared with Example 1, in Comparative Example 9, oxygen or air was not used as an oxidant during the secondary precipitation reaction, and the S content in the obtained hydrated iron phosphate material was 0.0175wt%; the specific surface area and tap density of the obtained iron phosphate material were both reduced, which were 6.35m 2 / g and 1.11g / cm 3 Compared with Example 1, in Comparative Example 1, no citric acid was added during the secondary precipitation reaction, and no oxygen or air was used as an oxidant. Thus, the impurity elements of the hydrated iron phosphate material obtained were higher, wherein the content of S element was 0.0331wt%. The specific surface area and tap density of the obtained iron phosphate material were both reduced, which were 6.32 m 2 / g and 1.09 g / cm 3 It can be seen that using only oxygen or air as an oxidant during the secondary precipitation reaction will increase the content of impurity elements in the obtained hydrated iron phosphate, and reduce the specific surface area and tap density of the obtained iron phosphate material; further, in the secondary precipitation reaction, neither oxygen or air is used as an oxidant nor citric acid is added, the impurity elements in the obtained hydrated iron phosphate will be further increased, the pore size distribution uniformity of the obtained iron phosphate material will be poor, and the specific surface area and tap density of the iron phosphate material will be further reduced.

[0112] Compared with Example 1, in Comparative Example 6, the same amount of citric acid as that in Example 1 was added in a precipitation process, and the content of impurity elements in the obtained hydrated iron phosphate material was higher, wherein the content of S element was 0.0195wt%, and the specific surface area and tap density of the obtained iron phosphate material were reduced, which were 7.05 m 2 / g and 1.18 g / cm 3 Since the addition of citric acid in the secondary precipitation reaction involves a dissolution and recrystallization process, the accumulation of impurity elements in the hydrated iron phosphate is reduced, and the iron phosphate material obtained has a more regular morphology and a uniform pore size distribution; adding citric acid in the primary reaction process cannot achieve the same effect.

[0113] Compared with Example 1, in Comparative Examples 7 and 8, during a precipitation reaction, the oxidation rate of ferrous ions in ferrous salts is lower than the specified range or higher than the specified range, and a hydrated ferric phosphate with a higher content of impurity elements is obtained, and an iron phosphate material with a lower specific surface area and a tap density is obtained. This is because in a precipitation reaction, the oxidation rate of ferrous ions is too low, the generated crystal seeds are few, the particle size of the second stage reaction will become larger, it is easy to wrap impurities, and the specific surface area will decrease; while the oxidation rate of ferrous ions in the first reaction is too high, and the precipitation growth process of the second reaction is uneven, which will lead to uneven pore distribution and a decrease in specific surface area. In addition, it can be seen from Comparative Example 2 that the amount of citric acid used is too low to prevent the deposition of impurities.

[0114] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An iron phosphate material, characterized in that: The iron phosphate material includes a porous outer layer; and the pore area ratio of micropores, mesopores and macropores of the iron phosphate material satisfies 10%-20%:55%-65%:20%-30%.

2. The iron phosphate material according to claim 1, characterized in that The iron phosphate material satisfies at least one of the following features 1-3: Feature 1: The specific pore volume of the iron phosphate material is 0.06-0.10cm 3 / g; Feature 2: The tap density of the iron phosphate material is 1.15-1.35 g / cm 3 ; Feature 3: The specific surface area of ​​the iron phosphate material is 6.40-7.30m 2 / g.

3. A method for preparing the iron phosphate material according to claim 1 or 2, characterized in that: The preparation method comprises: A primary precipitation reaction: partially oxidizing the ferrous ions in the ferrous salt solution into trivalent ferrous ions, and adding a portion of the phosphorus source to perform a primary precipitation reaction to obtain a primary slurry; Secondary precipitation reaction: adding citric acid to the primary slurry, then blowing in oxygen or air and adding the remaining phosphorus source to carry out secondary precipitation reaction, and after solid-liquid separation, washing and drying to obtain hydrated iron phosphate; Calcination: The hydrated ferric phosphate is calcined to obtain ferric phosphate material.

4. The preparation method according to claim 3, characterized in that: The partial oxidation refers to oxidizing 5%-20% of the ferrous ions in the ferrous salt solution into ferric ions; And / or, the sulfur content of the hydrated ferric phosphate is 0.0125wt%-0.0150wt%.

5. The preparation method according to claim 3, characterized in that: The amount of citric acid added is 1wt%-8wt% of the theoretical output of iron phosphate; Preferably, the amount of citric acid added is 1wt%-4wt% of the theoretical output of ferric phosphate.

6. The preparation method according to claim 3, characterized in that: The partial oxidation comprises adding hydrogen peroxide to the ferrous salt solution at a rate of 0.2-0.5 L / h; And / or, the blowing flow rate of the oxygen or air is 10-30 L / h.

7. The preparation method according to claim 3, characterized in that: The ferrous salt in the ferrous salt solution includes at least one of ferrous sulfate, ferrous chloride and ferrous nitrate; And / or, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium phosphate.

8. The preparation method according to claim 3, characterized in that: The concentration of iron in the ferrous salt solution is 0.8-1.2 mol / L; And / or, the molar ratio of phosphorus in the phosphorus source to iron in the ferrous salt solution is 1:1.0-1.

1.

9. The preparation method according to claim 3, characterized in that: The temperature of the first precipitation reaction and the second precipitation reaction is 90-98°C; And / or, the primary precipitation reaction includes keeping warm for 1-3 hours after stopping the feeding; And / or, the secondary precipitation reaction includes aging for 3-6 hours after stopping the feeding; And / or, the calcination temperature is 600-750° C., and the calcination time is 2-6 hours.

10. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material is prepared from the iron phosphate material in claim 1 or 2, or from the iron phosphate material prepared by any one of the preparation methods in claims 3-8.

Citation Information

Patent Citations

  • Method for protective treatment of lithium cathodes in lithium secondary batteries

    CN104617259A

  • Preparation method of battery level microporous spherical iron phosphate

    CN106744774A

  • Porous spherical iron phosphate, preparation method thereof and metal phosphate

    CN117263153A

Cited By

  • Preparation method of iron phosphate, lithium iron phosphate as well as preparation method and application of lithium iron phosphate

    CN122010073A